(untitled) (Research, Society and Development, 2022)
Klippel-Trenaunay syndrome is a rare congenital abnormality of variable clinical manifestations and still unknown etiological origin characterized in the patient by the triad: port-wine stain, varicose veins and bone and soft tissue hypertrophy. Such a condition predicts risk to pregnancy, considering the increase in complications such as hemorrhage and thrombosis. In addition to this problem, teenage pregnancy is an additional risk to the occurrence of pregnancy in patients with this syndrome, considering the potentiation of problems related to teenage pregnancy. This is a prospective study of the case report type, whose study will be of a teenager, 14 years old, pregnant, with Klippel-Trenaunay Syndrome. Data were collected using a protocol established by the researchers during monthly home visits and the information was subsequently analyzed. In general, a positive outcome was observed in this case, however, pregnancy in women with KTS, especially adolescents, requires caution and close monitoring, given the high risks that such a pathology can generate in this period.